Predictive ability of waist-to-hip-ratio and waist-to-height-ratio in relation to overweight/obesity in adolescents from Vojvodina (the Republic of Serbia) predictive ability of waist-to-hip-ratio and waist-to-height-ratio : Predictive Ability of Waist-to-Hip-Ratio and Waist-to-Height-Ratio - Rakić, Rada; Pavlica, Tatjana; Bjelanović, Jelena; Vasiljević, Perica (Progress in Nutrition, 2019)
Introduction/Aim Overweight in childhood is a risk factor for later diseases in adulthood. It is necessary to identify thresholds for anthropometric indexes for assessing obesity. The aim of our study was to explore the accuracy of waist-to-height ratio (WHtR) and waist-to-hip ratio (WHR) and for the first time proposes the optimal thresholds of these indices for identifying overweight/obesity in Serbian adolescents aged 11-15 years. Methods The cross-sectional study was conducted with 2391 adolescents. Anthropometric measurements included body height, weight, waist circumference and hip circumferences. The relation between WHR and WHtR and general obesity as defined by the International Obesity Task Force IOTF was investigated with nonparametric receiver operating characteristic (ROC) analysis. Results  Both of the indicators of central adiposity showed a higher mean in the group of children with exceeded weight. The correlation of WHtR and body mass index (BMI) was considerably greater than the correlation between WHR and BMI in both sexes. The WHtR was a better predictor of general obesity than the WHR in both boys and girls. The WHtR cut-offs of 0.464 for boys and 0.465 for girls, and 0.510 for boys and 0.504 for girls have been proposed to identify overweight and obesity, respectively, in Serbian adolescents. Conclusion  WHtR is an accurate index with high applicability to screening adolescents with excess weight.